Preparation method and application of copper nanocluster modified silver bromide nanoparticle / titanium dioxide photocatalyst

By orientedly modifying Cu nanoclusters and AgBr nanoparticles on the TiO2 substrate to form a Cu/AgBr/TiO2 ternary hybrid structure, the problem of difficulty in synthesizing C2H4 and H2O2 in the photoconversion of CO2 and H2O in the prior art is solved, and an efficient and stable photocatalytic reaction is achieved.

CN119549170AActive Publication Date: 2025-03-04JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411725396.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

In the photoconversion of low-cost CO2 and H2O, it is difficult for the prior art to synthesize high-value C2H4 and H2O2 simultaneously, and the large waste of photogenerated charges and spontaneous recombination of *H-*OH have resulted in hindering synthesis.

Method used

Through the ion exchange process strengthened by electrostatic interaction, a spatially confined ternary hybrid heterostructure was developed, and Cu nanocluster modified AgBr nanoparticles were oriented to the TiO2 substrate to form a Cu/AgBr/TiO2 ternary hybrid structure, realizing a cascaded multi-step charge transfer mechanism and efficient *H, *OH and *CO generation.

Benefits of technology

Efficient, stable and selective photo-driven CO2 and H2O conversion are achieved, which significantly improves the generation efficiency of C2H4 and H2O2, and inhibits *H-*OH recombination and reduces charge waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549170A_ABST
    Figure CN119549170A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite nanomaterials, and relates to a preparation method of a copper nanocluster modified silver bromide nanoparticle / titanium dioxide photocatalyst, which comprises the following steps: mixing a copper source and a silver source in deionized water to form a Cu ion adsorbed AgCl (Cu / AgCl) turbid solution; the preparation method comprises the following steps: dispersing TiO2, ascorbic acid, polyvinylpyrrolidone and potassium bromide in deionized water, carrying out uniform ultrasonic treatment, transferring into an oil bath, stirring, heating, adding a Cu / AgCl turbid solution, carrying out a reaction, washing and removing impurities, and thus obtaining the TiO2 / AgCl composite material. The photocatalyst disclosed by the invention is applied to photocatalytic conversion of CO2 and H2O to prepare C2H4 and H2O2. Through an ion exchange process enhanced by electrostatic interaction, AgBr nanoparticles modified by Cu nanoclusters are directionally modified on a TiO2 substrate. A spatial confinement structure and a Cu / AgBr / TiO2 ternary mixed structure have a cascaded multi-step charge transfer mechanism, strong charge driving force is provided for the catalyst, in addition, adjacent heteronuclear sites of Cu and Ag provide a high-quality synergistic catalysis effect for the whole reaction, and C2H4 and H2O2 are prepared by converting CO2 and H2O through light driving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite nanomaterials, relates to a photocatalyst, and in particular to a preparation method and application of a copper nanocluster modified silver bromide nanoparticle / titanium dioxide (Cu / AgBr / TiO2) photocatalyst. Technical Background

[0002] The use of natural light to drive the conversion of CO2 and H2O into chemicals with high economic added value (such as CO, CH4, CH3OH, C2H4, C2H6, O2, and H2O2) is considered an important strategy to alleviate the growing CO2 level and energy crisis. Among the various products produced by electron-mediated CO2 photoreduction, C2H4 is considered a high-value raw material, accounting for about 75% of petrochemical products in the chemical industry, while H2O2 is considered to be the most economically valuable product obtained from H2O oxidation reactions. Therefore, the simultaneous generation of photogenerated electrons for C2H4 production and photogenerated holes for H2O2 production can maximize the economic benefits of the products. However, the simultaneous synthesis of C2H4 and H2O2 in the low-cost photoconversion of CO2 and H2O has not yet been achieved.

[0003] The preparation of C2H4 and H2O2 involves the transfer of *CO, *H and *OH active species. High concentrations of active species usually facilitate the key steps of *CO dimerization, protonation and *OH coupling. Considering the charge carrier transfer kinetics and the thermodynamic characteristics of CO2 and H2O conversion, it is observed that photogenerated electrons can promote the transfer of hydrogen ions (H + ) and CO2 are reduced to generate *H and *CO, while the photogenerated holes can oxidize a large number of hydroxide ions (OH - ) to generate *OH, indicating that sufficient charge driving force contributes to the efficient synthesis of C2H4 and H2O2. However, the large demand for *H and *OH intermediates and the inherent contradiction of *H-*OH spontaneous recombination further lead to a large waste of photogenerated charges and hindered synthesis of C2H4 and H2O2. Therefore, in this highly economical carbon cycle reaction system, it is extremely important to accurately prepare photocatalysts with strong charge driving force with well-defined active sites.

[0004] The present invention develops a spatially confined ternary hybrid heterostructure through an ion exchange process enhanced by electrostatic interaction, and the AgBr nanoparticles modified by Cu nanoclusters are directionally modified onto a TiO2 substrate. Utilizing the spatially confined structure, the Cu / AgBr / TiO2 ternary hybrid structure has a cascaded multi-step charge transfer mechanism, providing a strong charge momentum to drive efficient *H, *OH and *CO production. In addition, in the present invention, the Cu nanoclusters act as efficient active centers for *OH species capture, greatly inhibiting *H-*OH recombination, and promoting the transfer and protonation reaction of *H. The Cu nanoclusters anchoring *OH can also effectively trigger the rapid transfer and accumulation of *CO derived from AgBr, promoting efficient *CO coupling reactions. In addition, since the high concentration of *OH coverage promotes *OH coupling, the light-driven conversion of CO2 and H2O to C2H4 and H2O2 is successfully achieved. Therefore, the present invention not only emphasizes the importance of a strong charge driving force for efficient mass transfer, but also emphasizes the importance of inhibiting *H-*OH recombination for promoting the co-photosynthesis of C2H4 and H2O2 from CO2 and H2O. Summary of the invention

[0005] In order to solve the problems and challenges involved in the above-mentioned technologies, the present invention provides a preparation method and application of a copper nanocluster modified silver bromide nanoparticle / titanium dioxide (Cu / AgBr / TiO2) photocatalyst.

[0006] Technical Solution

[0007] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide (Cu / AgBr / TiO2) photocatalyst comprises the following steps:

[0008] (1) Synthesis of Cu / AgCl: A copper source and a silver source are mixed in deionized water to form a Cu ion-adsorbed AgCl turbid solution, wherein the mass ratio of copper in the copper source to silver in the silver source is 0.001-0.020 g:0.002-0.030 g, preferably 0.018 g:0.020 g;

[0009] (2) Synthesis of Cu / AgBr / TiO2: TiO2, ascorbic acid, polyvinyl pyrrolidone and potassium bromide were dispersed in deionized water by ultrasonication, and then transferred to an oil bath at 50-100°C. After stirring and heating for 10 min, Cu / AgCl turbid solution was added and the reaction was maintained at 50-100°C for 3-5 h, preferably at 80°C for 3 h. The mixture was taken out and naturally cooled to room temperature, and then washed with deionized water and anhydrous ethanol to remove impurities. The mass-to-volume ratio of TiO2, ascorbic acid, polyvinyl pyrrolidone, potassium bromide and deionized water was 0. 100~0.500g:0.100~0.200g:0.100~0.200g:0.300~0.500g:4.000~20.000mL, preferably 0.200g:0.105g:0.120g:0.300g:12.000mL; the mass ratio of copper in the copper source, silver in the silver source, and TiO2 is: 0.001~0.020g:0.002~0.030g:0.100~0.500g, preferably 0.018g:0.020g:0.200g.

[0010] According to a preferred embodiment of the present invention, in step (1), when the copper source is a nitrate or sulfate of copper, specifically copper nitrate, cuprous nitrate, copper sulfate, cuprous sulfate, preferably copper nitrate, and the silver source is silver chloride; when the copper source is a hydrochloride, specifically cupric chloride or cuprous chloride, preferably cupric chloride, and the silver source is silver nitrate.

[0011] The copper nanocluster-modified silver bromide nanoparticles / titanium dioxide (Cu / AgBr / TiO2) photocatalyst prepared by the method disclosed in the present invention has the morphology of copper nanoclusters modified on the surface of silver bromide nanoparticles and co-loaded on the surface of granular titanium dioxide.

[0012] The microscopic morphology of the Cu nanoclusters and AgBr nanoparticles prepared in the present invention is observed by transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM), the composition structure is confirmed by X-ray diffraction (XRD), and the atomic coordination environment is analyzed by synchrotron radiation X-ray absorption spectroscopy (XAFS).

[0013] Another object of the present invention is to apply the prepared copper nanocluster modified silver bromide nanoparticles / titanium dioxide photocatalyst (Cu / AgBr / TiO2) to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2.

[0014] Photocatalytic CO2 reduction and H2O oxidation performance tests

[0015] (1) 2.0 mg of the photocatalyst was dispersed on the surface of a microporous membrane with a radius of 2.35 cm, and 0.5 mL of deionized water was added to the reaction system as a hole consuming agent. In addition, the gas circulation system was vacuum treated for 15 min, and then filled with high-purity CO2 gas (99.99%) to 90 kPa, and vacuum treated again, and then CO2 was refilled into the reaction system to maintain the pressure at 90 kPa;

[0016] (2) The light source is a 300W xenon lamp, and the actual catalyst surface irradiation intensity is 400mW·cm -2 The gas products were detected by a gas chromatograph equipped with a flame ionization detector (FID) and a thermal conductivity detector (TCD). The generated gas was calibrated with a standard gas mixture, and its composition was qualitatively and quantitatively analyzed by retention time and peak intensity, respectively. The photocatalytic activity experiment was carried out by reducing CO2 by xenon lamp irradiation. The type of reduction product was determined by gas chromatography retention time, and the CO2 reduction efficiency was determined by comparing the measured peak area with the standard peak area to evaluate its photocatalytic CO2 reduction performance.

[0017] (3) Through Ce 4+ The titration method is used to detect the amount of H2O2 generated. This method is based on the 4+ The reaction between Ce 4+ Reducing to Ce 3+ , causing the color to change from yellow to colorless. 4+ The concentration was measured at 316 nm using a UV-Vis spectrophotometer. In the experiment, 5 mL of the gaseous product was injected into a solution containing Ce(SO4)2 (1 mM) and sulfuric acid (0.5 M). In addition, a solution of Ce(SO4)2 (1 mM) and sulfuric acid (0.5 M) was added to the reactor to collect H2O2 adsorbed on the reactor wall and in liquid H2O. The actual H2O2 quantification was performed by considering the total amount of H2O2 in the gas and liquid phases.

[0018] Beneficial Effects

[0019] The present invention develops a spatially confined ternary hybrid heterostructure through an ion exchange process enhanced by electrostatic interaction, and the AgBr nanoparticles modified by Cu nanoclusters are directionally modified on a TiO2 substrate. Utilizing the spatially confined structure, the Cu / AgBr / TiO2 ternary hybrid structure has a cascaded multi-step charge transfer mechanism, which provides a strong charge driving force for the catalyst. In addition, the adjacent heteronuclear sites of Cu and Ag provide a high-quality synergistic catalytic effect for the entire reaction, achieving efficient, stable, and highly selective light-driven CO2 and H2O conversion to C2H4 and H2O2. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 .(a) TEM image of Cu / AgBr / TiO2;(b) HRTEM image of Cu / AgBr / TiO2;

[0021] Figure 2 .XRD patterns of TiO2, AgCl, Cu / TiO2, AgBr / TiO2, Cu / AgBr / TiO2;

[0022] Figure 3 .(a) XANES analysis of Cu K-edge of Cu / AgBr / TiO2 and (d) Ag K-edge of Cu / AgBr / TiO2; (b) k3-weighted FT-EXAFS spectrum fitting analysis of Cu K-edge of Cu / AgBr / TiO2 and (e) Ag K-edge of Cu / AgBr / TiO2; (c) Experimental and fitted EXAFS curves of Cu K-edge of Cu / AgBr / TiO2 and (f) Ag K-edge spectra of Cu / AgBr / TiO2 in R space and k space;

[0023] Figure 4 .(a) Comparison of CO2 photosynthesis C2 chemicals and hydrogen peroxide performance of TiO2, AgBr, Cu / AgBr, AgBr / TiO2, Cu / TiO2, and Cu / AgBr / TiO2; (b) Photocatalytic CO2 conversion stability test of Cu / AgBr / TiO2. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0025] Example 1

[0026] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0027] (1) Preparation of Cu / AgCl

[0028] 0.048 g of CuCl2·2H2O and 0.031 g of AgNO3 were added to 4 mL of deionized water to form a turbid AgCl solution with Cu ions adsorbed, in which the mass of Cu was 0.018 g and the mass of Ag was 0.020 g;

[0029] (2) Preparation of Cu / AgBr / TiO2

[0030] 0.200 g TiO2, 0.120 g ascorbic acid, 0.105 g polyvinyl pyrrolidone, and 0.300 g potassium bromide were dispersed in 8 mL deionized water, ultrasonically treated for 10 min, transferred to an oil bath at 80 °C and stirred continuously. After heating for 10 min, the above Cu / AgCl turbid solution was added and kept at 80 °C for 3 h. The sample was taken out and naturally cooled to room temperature. The sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0031] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to C2H4 and H2O2, which not only showed a high photocatalytic activity of 162.4 μmol·g -1 ·h -1 of C2H4 and 74.6 μmol·g -1 ·h -1 The C2H6 production efficiency is as high as 686.3 μmol·g -1 ·h -1 , C2 products and H2O2 are higher than those of TiO2, AgBr, Cu / AgBr, Cu / TiO2, and AgBr / TiO2 series catalysts.

[0032] The prepared material characterization and specific analysis are as follows:

[0033] like Figure 1 As shown in (a) and 1(b), in the Cu / AgBr / TiO2 ternary heterostructure, the TEM image shows that commercial TiO2 is a small-sized nanoparticle, AgBr is a large-sized nanoparticle, and HRTEM shows lattice fringe spacings of 0.207nm, 0.199nm, and 0.291nm. Figure 2 Further XRD analysis showed that the three crystal plane spacings correspond to the (111) crystal plane of Cu nanoclusters, the (220) crystal plane of AgBr nanoparticles, and the (211) crystal plane of TiO2 nanoparticles, respectively, and the interfaces between different components are clear, indicating that the strong electrostatic adsorption effect during the ion exchange process can effectively promote the successful construction of Cu / AgBr / TiO2 ternary heterojunction catalyst with a spatial separation structure.

[0034] like Figure 3 (a) Figure 3 (b) Figure 3 As shown in (c), Cu atoms mainly contribute to the coordination with Cu atoms and Ag atoms, rather than in the form of Cu-O bonding, indicating that the Cu nanoclusters are tightly connected to the AgBr component and have no direct bonding with the TiO2 substrate.

[0035] like Figure 3 (d) Figure 3 (e) Figure 3As shown in (f), the Ag atoms mainly exist in the Ag-Br coordination configuration, and there is an Ag-Cu coordination contribution, which further indicates the successful construction of a ternary heterojunction catalyst with a spatially confined structure.

[0036] Comparative Example 1

[0037] A method for preparing AgBr nanoparticles / titanium dioxide photocatalyst (AgBr / TiO2) comprises the following steps:

[0038] 0.200 g TiO2, 0.120 g ascorbic acid, 0.105 g polyvinyl pyrrolidone, and 0.300 g potassium bromide were dispersed in 8 mL deionized water, and the mixture was ultrasonically treated for 10 min; the above solution was further transferred to an oil bath at 80°C, and after continuous stirring and heating for 10 min, 0.031 g AgNO3 was added to the TiO2 mixture, the solution was maintained at 80°C for 3 h, and the sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0039] The prepared AgBr / TiO2 exhibited a high -1 ·h -1 of C2H4 and 5.8 μmol·g -1 ·h -1 The C2H6 preparation efficiency and C2H4 preparation efficiency are 33.2 and 49.3 times that of monomeric AgBr and TiO2, respectively.

[0040] Comparative Example 2

[0041] A method for preparing a Cu nanocluster / titanium dioxide photocatalyst (Cu / TiO2) comprises the following steps:

[0042] 0.200 g TiO2, 0.120 g ascorbic acid, 0.105 g polyvinyl pyrrolidone, and 0.300 g potassium bromide were dispersed in 8 mL deionized water, and the mixture was ultrasonically treated for 10 min; the above solution was further transferred to an oil bath at 80°C, and after continuous stirring and heating for 10 min, 0.048 g CuCl2·2H2O was added to the TiO2 mixture, the solution was maintained at 80°C for 3 h, and the sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0043] The prepared Cu / TiO2 exhibited a 20.0 μmol·g -1 ·h -1 of C2H4 and 15.6 μmol·g -1 ·h -1 The C2H6 preparation efficiency and C2H4 preparation efficiency are 69.0 times that of monomer TiO2.

[0044] Comparative Example 3

[0045] A method for preparing a Cu / AgBr composite catalyst comprises the following steps:

[0046] (1) Preparation of Cu / AgCl

[0047] 0.048 g of CuCl2·2H2O and 0.031 g of AgNO3 were added to 4 mL of deionized water to form a turbid AgCl solution with Cu ions adsorbed, in which the mass of Cu was 0.018 g and the mass of Ag was 0.020 g;

[0048] (2) Preparation of Cu / AgBr

[0049] 0.120 g of ascorbic acid, 0.105 g of polyvinyl pyrrolidone, and 0.300 g of potassium bromide were dispersed in 8 mL of deionized water, and the mixture was ultrasonically treated for 10 min; it was further transferred to an oil bath at 80°C and stirred and heated for 10 min, and then Cu / AgCl was added to the mixture; the solution was kept at 80°C for 3 h, and the sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0050] The prepared Cu / AgBr exhibited a high -1 ·h -1 of C2H4 and 0.7 μmol·g -1 ·h -1 The C2H6 preparation efficiency and C2H4 preparation efficiency are 4.9 times that of monomer AgBr.

[0051] Comparative Example 4

[0052] A method for preparing AgBr nanoparticles comprises the following steps:

[0053] 0.100 g of AgNO3, 0.120 g of ascorbic acid, 0.105 g of polyvinyl pyrrolidone, and 0.300 g of potassium bromide were dispersed in 8 mL of deionized water, the mixture was ultrasonically treated for 10 min, the solution was maintained at 80 °C for 3 h, and the sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0054] The prepared AgBr exhibited a 0.4 μmol·g -1 ·h -1 of C2H4 and 0.6 μmol·g -1 ·h -1 The C2H6 preparation efficiency.

[0055] The performance test of the photocatalysts prepared in the above embodiments is specifically analyzed as follows:

[0056] like Figure 4(a) Compared with pure TiO2, TiO2 composite photocatalysts show significant improvement in the performance of CO2 photosynthesis of multi-carbon chemicals. Based on the synergistic optimization of Cu nanoclusters and AgBr nanoparticles in the process of light-driven CO2 and H2O conversion, Cu / AgBr / TiO2 shows the highest C2H4 and C2H6 activity, showing 162.4 μmol·g -1 ·h -1 of C2H4 and 74.6 μmol·g -1 ·h -1 The C2H6 production efficiency is as high as 686.3 μmol·g -1 ·h -1 , C2 products and H2O2 are higher than those of TiO2, AgBr, Cu / AgBr, Cu / TiO2, and AgBr / TiO2 series catalysts.

[0057] Figure 4 (b) shows that the Cu / AgBr / TiO2 composite photocatalyst did not show obvious performance degradation during the 24-hour test, indicating that the composite photocatalyst has excellent catalytic stability and green sustainable development potential.

[0058] Example 2

[0059] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0060] (1) Preparation of Cu / AgCl

[0061] 0.005 g of CuCl2·2H2O and 0.005 g of AgNO3 were added to 4 mL of deionized water to form a turbid AgCl solution with Cu ions adsorbed, in which the mass of Cu was 0.002 g and the mass of Ag was 0.003 g;

[0062] (2) Preparation of Cu / AgBr / TiO2

[0063] 0.100 g TiO2, 0.100 g ascorbic acid, 0.100 g polyvinyl pyrrolidone, and 0.300 g potassium bromide were dispersed in 4 mL deionized water, ultrasonically treated for 10 min, transferred to a 50 °C oil bath and stirred continuously. After heating for 10 min, the above Cu / AgCl turbid solution was added and kept at 50 °C for 3 h. The sample was taken out and naturally cooled to room temperature, and washed three times with deionized water and anhydrous ethanol to remove impurities.

[0064] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2, with a C2H4 production rate of 81.4 μmol·g -1 ·h -1 , the C2H6 production efficiency is 35.2 μmol·g -1 ·h -1 The H2O2 generation efficiency is 316.7 μmol·g -1 ·h -1 .

[0065] Example 3

[0066] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0067] (1) Preparation of Cu / AgCl

[0068] 0.020 g of CuCl2·2H2O and 0.030 g of AgNO3 were added to 4 mL of deionized water to form a turbid AgCl solution with Cu ions adsorbed, in which the mass of Cu was 0.007 g and the mass of Ag was 0.019 g;

[0069] (2) Preparation of Cu / AgBr / TiO2

[0070] 0.500 g TiO2, 0.200 g ascorbic acid, 0.200 g polyvinyl pyrrolidone, and 0.500 g potassium bromide were dispersed in 20 mL deionized water, ultrasonically treated for 10 min, transferred to an oil bath at 100 °C and stirred continuously. After heating for 10 min, the above Cu / AgCl turbid solution was added and kept at 100 °C for 5 h. The sample was taken out and naturally cooled to room temperature, and washed three times with deionized water and anhydrous ethanol to remove impurities.

[0071] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2, with a C2H4 production rate of 98.6 μmol·g -1 ·h -1 , the C2H6 production efficiency is 52.4 μmol·g -1 ·h -1 The H2O2 generation efficiency was 573.6 μmol·g -1 ·h -1 .

[0072] Example 4

[0073] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0074] (1) Preparation of Cu / AgCl

[0075] 0.020 g of Cu(NO3)2 and 0.015 g of AgCl were added to 4 mL of deionized water to form a Cu ion-adsorbed AgCl turbid solution, in which the mass of Cu was 0.007 g and the mass of Ag was 0.011 g;

[0076] (2) Preparation of Cu / AgBr / TiO2

[0077] 0.200 g TiO2, 0.120 g ascorbic acid, 0.105 g polyvinyl pyrrolidone, and 0.300 g potassium bromide were dispersed in 8 mL deionized water, ultrasonically treated for 10 min, transferred to an oil bath at 80 °C and stirred continuously. After heating for 10 min, the above Cu / AgCl turbid solution was added and kept at 80 °C for 3 h. The sample was taken out and naturally cooled to room temperature. The sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0078] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2, with a C2H4 production rate of 133.5 μmol·g -1 ·h -1 The C2H6 production efficiency is 42.7 μmol·g -1 ·h -1 The H2O2 generation efficiency is 396.5 μmol·g -1 ·h -1 .

[0079] Example 5

[0080] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0081] (1) Preparation of Cu / AgCl

[0082] 0.040 g of CuCl and 0.031 g of AgNO3 were added to 4 mL of deionized water to form a turbid AgCl solution adsorbed with Cu ions, in which the mass of Cu was 0.026 g and the mass of Ag was 0.020 g;

[0083] (2) Preparation of Cu / AgBr / TiO2

[0084] 0.300 g TiO2, 0.150 g ascorbic acid, 0.150 g polyvinyl pyrrolidone, and 0.400 g potassium bromide were dispersed in 12 mL deionized water, ultrasonically treated for 10 min, transferred to an oil bath at 90 °C and stirred continuously, heated for 10 min, and then added with the above Cu / AgCl turbid solution, maintained at 90 °C for 3 h, taken out and naturally cooled to room temperature, and the sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0085] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2, with a C2H4 production rate of 108.4 μmol·g -1 ·h -1 , the C2H6 production efficiency is 33.2 μmol·g -1 ·h -1 The H2O2 generation efficiency was 224.6 μmol·g -1 ·h -1 .

[0086] Example 6

[0087] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0088] (1) Preparation of Cu / AgCl

[0089] 0.050 g of CuSO4·5H2O and 0.015 g of AgCl were added to 4 mL of deionized water to form a Cu ion-adsorbed AgCl turbid solution, in which the mass of Cu was 0.013 g and the mass of Ag was 0.011 g;

[0090] (2) Preparation of Cu / AgBr / TiO2

[0091] 0.150 g TiO2, 0.120 g ascorbic acid, 0.120 g polyvinyl pyrrolidone, and 0.350 g potassium bromide were dispersed in 10 mL deionized water, ultrasonically treated for 10 min, transferred to a 90 °C oil bath and stirred continuously. After heating for 10 min, the above Cu / AgCl turbid solution was added, maintained at 90 °C for 3 h, taken out and naturally cooled to room temperature, and the sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0092] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2, with a C2H4 production rate of 173.4 μmol·g -1 ·h -1 The C2H6 production efficiency is 52.6 μmol·g -1 ·h-1 The H2O2 generation efficiency is 368.7 μmol·g -1 ·h -1 .

[0093] Example 7

[0094] A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst (Cu / AgBr / TiO2) comprises the following steps:

[0095] (1) Preparation of Cu / AgCl

[0096] 0.030 g of CuNO3 and 0.015 g of AgCl were added to 4 mL of deionized water to form a Cu ion-adsorbed AgCl turbid solution, in which the mass of Cu was 0.015 g and the mass of Ag was 0.011 g;

[0097] (2) Preparation of Cu / AgBr / TiO2

[0098] 0.250 g TiO2, 0.150 g ascorbic acid, 0.150 g polyvinyl pyrrolidone, and 0.450 g potassium bromide were dispersed in 10 mL deionized water, ultrasonically treated for 10 min, transferred to an oil bath at 100 °C and stirred continuously. After heating for 10 min, the above Cu / AgCl turbid solution was added and kept at 100 °C for 3 h. The sample was taken out and naturally cooled to room temperature. The sample was washed three times with deionized water and anhydrous ethanol to remove impurities.

[0099] The prepared Cu / AgBr / TiO2 was applied to photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2, with a C2H4 production rate of 152.7 μmol·g -1 ·h -1 The C2H6 production efficiency is 43.2 μmol·g -1 ·h -1 The H2O2 generation efficiency was 297.6 μmol·g -1 ·h -1 .

[0100] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst, characterized in that: The steps include: (1) mixing a copper source and a silver source in deionized water to form a Cu ion-adsorbed AgCl turbid solution, i.e., a Cu / AgCl turbid solution, wherein the mass ratio of copper in the copper source to silver in the silver source is 0.001-0.020 g: 0.002-0.030 g; (2) Dispersing TiO2, ascorbic acid, polyvinyl pyrrolidone and potassium bromide in deionized water by ultrasonic treatment, transferring to an oil bath at 50-100°C, stirring and heating for 10 minutes, adding the Cu / AgCl turbid solution, maintaining the temperature at 50-100°C for reaction for 3-5 hours, taking out and cooling naturally to room temperature, washing with deionized water and anhydrous ethanol to remove impurities, and obtaining the obtained product; wherein the mass-volume ratio of TiO2, ascorbic acid, polyvinyl pyrrolidone, potassium bromide and deionized water is 0.100-0.500g: 0.100-0.200g: 0.100-0.200g: 0.300-0.500g: 4.000-20.000mL, preferably 0.200g: 0.105g: 0.120g: 0.300g: 12.000mL; the mass ratio of copper in the copper source, silver in the silver source, and TiO2 is: 0.001~0.020g: 0.002~0.030g: 0.100~0.500g, preferably 0.018 g: 0.020 g: 0.200g.

2. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 1, characterized in that: In step (1), the mass ratio of copper in the copper source to silver in the silver source is 0.018 g:0.020 g.

3. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 1, characterized in that: In step (1), when the copper source is copper nitrate or sulfate, the silver source is silver chloride.

4. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 3, characterized in that: In step (1), the copper source is copper nitrate, cuprous nitrate, copper sulfate or cuprous sulfate.

5. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 4, characterized in that: In step (1), the copper source is copper nitrate.

6. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 1, characterized in that: In step (1), when the copper source is hydrochloride, the silver source is silver nitrate.

7. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 6, characterized in that: In step (1), the copper source is cupric chloride or cuprous chloride, preferably cupric chloride.

8. The method for preparing the copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst according to claim 1, characterized in that: In step (2), the Cu / AgCl turbid solution is added and kept at 80° C. for 3 hours.

9. The copper nanocluster-modified silver bromide nanoparticle / titanium dioxide photocatalyst prepared according to any one of claims 1 to 8, characterized in that: The photocatalyst has the morphology of copper nanoclusters modified on the surface of silver bromide nanoparticles, which are jointly loaded on the surface of granular titanium dioxide.

10. An application of the copper nanocluster modified silver bromide nanoparticles / titanium dioxide photocatalyst as claimed in claim 9, characterized in that: It is applied to the photocatalytic conversion of CO2 and H2O to produce C2H4 and H2O2.

Citation Information

Patent Citations

  • Application of silver halide composite materials in preparing carbon dioxide into hydrocarbon under visible-light catalysis

    CN102068999A

  • Preparation method of silver halide composite material

    CN102614898A

  • Preparation method and application of copper monatomic anchored gold nanocluster / titanium dioxide photocatalyst

    CN118287101A